THE EFFICIENCY OF COMMERCIAL BANKS IN INDONESIA (CASE STUDY 19 COMMERCIAL BANKS IN INDONESIA PERIOD 2008-2017) - Shubhi, Muhammad Miftahus; Anggono, Achmad Herlanto (Journal of Business and Management, 2018)
Abstract. Background: . The purpose of this research is to analyze the technical eficiency of the commercial banks in Indonesia from 2008 until 2017. This research used 19 commercial banks that listed on BUKU 3 and BUKU 4 in Indonesia. Methods: Non-parametric Data Envelopment Analysis (DEA) was calculated using intermediation approach, output oriented, and using Variable return to scale (VRS). This research using total deposits, fixed asset, and price of labor as the input and using total loan and income as the output. Results: The result of this research shows that Only BRI, MANDIRI, MIZUHO and SUMITOMO MITSUI have 100% of efficiency from 2008 to 2017, meanwhile BNI, BJB, MAYBANK, OCBC and MEGA never reach 100% of efficiency in the same period. Conclusion: not all the commercial banks from BUKU 3 and BUKU 4 already efficient, and for the others banks in this research can use BRI, MANDIRI, MIZUHO and SUMITOMO MITSUI as the bencmark to keep the bank efficiency. In th eother hand, all of those banks may have to increase 6,8% of the output to reach the effciency score without requiring the additional input.Keywords: Efficiency, Banking, Data Envelopment Analysis